PERSEPSI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN UNP MENGGUNAKAN PROGRAM AUTOCAD 2007 - Riko Fernando Putra; Yaumal Arbi (Teknik Sipil Universitas Negeri Padang, 2021)
This research was motivated by the existence of various opinions on the limited knowledge and abilities of students during the 2007 AutoCAD program learning process by students of the Building Engineering Education Study Program. The purpose of this study was to reveal the students' perceptions of the Building Engineering Education Study Program UNP using the AutoCAD 2007 program. This type of research is a descriptive study using a quantitative approach. This research was conducted in the Civil Engineering Department, Faculty of Engineering, UNP in March 2021. The sample used in this study were 85 prospective students of the 2017 UNP Building Engineering Education Study Program. The data collection technique used is by distributing online questionnaires by distributing questionnaire links that have been created using the help of the Google Form container then the Questionnaire Links are sent through the Whattsap media application for each sample that has been determined. The data analysis technique in this research is data verification using Microsoft Excel 2013 and descriptive analysis using SPSS V.17. Based on the results of the research that has been done, it can be concluded that the Student Perceptions of the Building Engineering Education Study Program Using the AutoCAD 2007 Program are Classified as Good with a percentage level of achievement degrees of 84.33%.